2018
DOI: 10.1016/j.jcbs.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Psychological inflexibility and stigma: A meta-analytic review

Abstract: Stigma is known to have major impacts on the physical and psychological health of many groups. Psychological inflexibility is a psychological process that may help explain the impact of stigma on both self and others. Accordingly, acceptance and commitment therapy (ACT), which targets psychological inflexibility, has been researched as a potential treatment for stigma. In order to provide a comprehensive overview of these issues, this paper offers a systematic review and meta-analysis of the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 84 publications
2
23
0
3
Order By: Relevance
“…Theoretically, the core therapeutic processes of ACT are intended to enable people with pain to contact negative judgements and interactions with openness and wider awareness, and to not take them to heart, so to speak. 34 Given the demonstrated benefits of ACT for emotional, physical, and social functioning, one might predict that this could reduce instances of stigmatizing behaviour from others. This is based on the reasoning that better, healthier, functioning might make others unable to detect reflections of pain, distress, and disability on which they can impose negative judgements and interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the core therapeutic processes of ACT are intended to enable people with pain to contact negative judgements and interactions with openness and wider awareness, and to not take them to heart, so to speak. 34 Given the demonstrated benefits of ACT for emotional, physical, and social functioning, one might predict that this could reduce instances of stigmatizing behaviour from others. This is based on the reasoning that better, healthier, functioning might make others unable to detect reflections of pain, distress, and disability on which they can impose negative judgements and interactions.…”
Section: Discussionmentioning
confidence: 99%
“…62 Another hypothesis is that ACT might not directly affect cognitive or emotional content related to stigma as measured by the SSCI-8, but rather it improves engagement in more adaptive behaviours in the presence of these experiences. 34 Finally, it may be that a general approach within ACT for chronic pain is not specifically targeted enough to impact stigma, and perhaps more specific customizing of ACT for stigma is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the original AAQ (Hayes et al, 2004) and AAQ-II (Bond et al, 2011) are very commonly used in ACT research (e.g., Bluett, Homan, Morrison, Levin, & Twohig, 2014;Krafft, Ferrell, Levin, & Twohig, 2018), recent studies have suggested that the AAQ-II has excessive overlap with distress (e.g., Francis et al, 2016;Rochefort, Baldwin, & Chmielewski, 2018). As the AAQH was developed based on the AAQ-II and uses similar items, it is possible that it also has excessive overlap with general distress or with hoarding symptoms specifically.…”
Section: Discussionmentioning
confidence: 99%
“…ACTr procedures have been shown to reduce prejudice across different domains, with varying populations and practices (Krafft, Ferrell, Levin, & Twohig, 2018). A few promising behavior-analytic interventions may also reduce racial bias or attenuate the effects of bias.…”
Section: Specific Interventionsmentioning
confidence: 99%